Development of A Comprehensive Instrument for The Islamic Education Subject Examination - Sarea, Muh Syahrul; Dewantara, Andi Harpeni; Sabbar, Sabbar Dahham (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This study aims to develop a comprehensive instrument for the Islamic Education course examination. Because the implementation of the Comprehensive Examination is still partial, flexible, and not yet supported by an instrument that has gone through a systematic quality testing process, it employs a research and development (R&D) approach, adopting a modified version of the Borg and Gall development model, which consists of seven stages: (1) research and information gathering, (2) planning, (3) development of the initial product, (4) limited trial, (5) revision of the initial product, (6) field testing, and (7) final product revision. Data were collected through interview guidelines and questionnaires to examine the theoretical and empirical characteristics of the test items. Data analysis was conducted using the R Studio application to determine item discrimination, difficulty level, and distractor effectiveness. The results indicate that the final product consists of 5 difficult items (25%), 12 moderate items (60%), and three easy items (15%). In terms of item discrimination, eight items (40%) were classified as very good, seven items (35%) as good, and five items (25%) as requiring revision. Regarding distractor effectiveness, 17 items (85%) were categorized as good, while three items (15%) were considered requiring revision. Based on the development of comprehensive instruments, the Islamic Education course shows good quality and is suitable for use.